PENGARUH ORGANIZATIONAL CULTURE TERHADAP FINANCIAL PERFORMANCE MELALUI LEARNING ORGANIZATION SEBAGAI VARIABEL MEDIASI - Lidea Rofianti; Devie Devie Devie (Business Accounting Review, 2018)
The aim of this study is to examine the effect of organizational culture on financial performance through learning organization as intervening variable. Besides that, this study examined the indirect effect of organizational culture on financial performance through learning organization as intervening variable. In this study, 33 manufacturing companies located in Surabaya and surrounding areas were chosen to be sample of the study. Data were collected from distribution of questionnaires and analyzed by using WarpPLS software version 5.0.The result showed that organizational culture has a significant positive impact on financial performance, organizational culture has a significant positive impact on learning organization, and learning organization has a significant positive impact on financial performance. The learning organization was the intervening variable of organizational culture on financial performance.